PRACTICE OF SELECTIVE CHOLINERGIC ANTAGONISTS IN PERIODIC FEVER TREATMENT IN CHILDREN - S.B. Krutikhina; A.V. Gorelov; M.A. Ratnikova ("Paediatrician" Publishers LLC, 2011)
Periodic fever - is a hereditary autosomal - recessive disease that is characterized by recurrent serositis and frequent amyloidosis development. One of the most common symptoms of this disease is abdominal pain. This article contains modern approach to pathogenesis, diagnostics and treatment of periodic fever. There is also a correlation analysis of dependence of periodic fever clinical course from gene MEFV mutation, as well as practice of selective M-cholinergic antagonist gioscine buthilbromide for abdominal pain relief in children and adolescents. Key words: periodic fever, abdominal pain, gioscine buthilbromide. (Voprosy sovremennoi pediatrii - Current Pediatrics. - 2011; 10 (5): 138-142.)